PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA CAFÃ‰ JUS GEBOY DI KECAMATAN PRAJEKAN BONDOWOSO - Darmawan, Rivanto Dwi; Ediyanto, Ediyanto; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Service quality is an important factor and root that is able to provide satisfaction for consumers. So that customers are satisfied with the services provided. The purpose of this study was to determine the effect of service quality on consumer satisfaction and purchasing decisions. This study uses primary data sourced from direct observation and questionnaires distributed to respondents, the sampling technique is determined by Probability Sampling. Data analysis and hypothesis testing in this study used the Structural Equation - Partial Lest Square (PLS-SEM) model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that service quality has a significant effect on purchasing decisions, service quality has a significant effect on consumer satisfaction, purchase decisions have a positive but not significant effect. The results of the indirect effect hypothesis test show that the service quality variable on consumer satisfaction through purchasing decisions has a positive but not significant effect.